In-Depth Insight into the Effect of Hydrophilic-Hydrophobic Group Designing in Amidinium Salts for Perovskite Precursor Solution on Their Photovoltaic Performance - Guohua Wu; Hua Li; Shuai Chen; Shengzhong (Frank) Liu; Yaohong Zhang; Dapeng Wang (Nanomaterials, 2022)
Amidinium salts have been utilized in perovskite precursor solutions as additives to improve the quality of perovskite films. The design of hydrophilic or hydrophobic groups in amidinium salts is of great importance to photovoltaic device performance and stability in particular. Here we report a contrast study of a guanidinium iodide (GUI) additive with a hydrophilic NH2 group, and a N,1–diiodoformamidine (DIFA) additive with a hydrophobic C–I group, to investigate the group effect. The addition of GUI or DIFA was beneficial to achieve high quality perovskite film and superior photovoltaic device performance. Compared with GUI, the addition of the DIFA in a perovskite precursor solution enhanced the crystal quality, reduced the defect density, and protected the water penetration into perovskite film. The perovskite solar cell (PSC) devices showed the best power conversion efficiency (PCE) of 21.19% for those modified with DIFA, as compared to 18.85% for the control, and 20.85% for those modified with GUI. In benefit to the hydrophobic C–I group, the DIFA–modified perovskite films and PSC exhibited the best light stability, thermal stability, and humidity stability in comparison to the control films and GUI–modified films. Overall, the introduction of a hydrophobic group in the amidinium salts additive was demonstrated to be an efficient approach to achieve high quality and stable perovskite film and PSC devices.